2016
DOI: 10.1377/hlthaff.2016.0708
|View full text |Cite
|
Sign up to set email alerts
|

Government Spending In Health And Nonhealth Sectors Associated With Improvement In County Health Rankings

Abstract: There is little evidence to demonstrate the impact on local health outcomes of spending that occurs outside the health care sector. We leveraged novel data from the US Census Bureau to measure the independent impact of a community's health and nonhealth expenditures on a broad measure of overall health-the County Health Rankings-over time. Using lagged longitudinal models that accounted for correlations of health outcomes and expenditures within counties, we found significant positive associations between expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 20 publications
5
58
0
Order By: Relevance
“…Public programs of social protection register more relative importance than public health care expenditure in explaining life expectancy at birth. The positive influence of social expenditure on health outcomes has been identified previously by Stuckler et al [86], Bradley et al [40,87], Vavken et al [88], and McCullough and Leider [89]. On the other hand, health expenditure financed by the government is in the last position in terms of relative importance.…”
Section: Discussionmentioning
confidence: 62%
“…Public programs of social protection register more relative importance than public health care expenditure in explaining life expectancy at birth. The positive influence of social expenditure on health outcomes has been identified previously by Stuckler et al [86], Bradley et al [40,87], Vavken et al [88], and McCullough and Leider [89]. On the other hand, health expenditure financed by the government is in the last position in terms of relative importance.…”
Section: Discussionmentioning
confidence: 62%
“…McCullough & Leider (71) have recently shown that annual county-level estimates may be constructed by interpolating missing data for each government within a county area. Larger governments are sampled more frequently than smaller ones; most report yearly.…”
Section: Per Capita Expenditure (Dollars)mentioning
confidence: 99%
“…Larger governments are sampled more frequently than smaller ones; most report yearly. As such, the approach may be reliable over time and is shown in Figure 3 (71).…”
Section: Per Capita Expenditure (Dollars)mentioning
confidence: 99%
“…Compared with the United States, other high-income country populations also tend to have better access (i.e., availability and affordability) to the health care system, and they use [30,31] and invest comparatively more in social services and public policies to promote health. Such investment in health and social services is associated with better population health in peer countries [35], as well as among specific U.S. subpopulations with these investments [36].…”
Section: Understanding the Us Health Disadvantagementioning
confidence: 99%